Pengaruh Uang Saku Dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa - Yola Armelia; Agus Irianto (Jurnal Ecogen, 2021)
Human needs always change according to the demands of the times, college students consume goods and services to meet their daily needs. College student income can come from pocket money given by family, scholarships and wages (while working). The action of college students consuming goods and services excessively (wasteful) is consumptive behavior. Factors supporting consumptive behavior include pocket money and lifestyle is defined as how a person does activities, has opinions and has interests. This study aims to determine the effect of pocket money and lifestyle on consumptive behavior in college students of the Faculty of Economics, Padang State of University. This study uses Path Analysis, the results of this study are the factor of pocket money and lifestyle proving that there is a positive and significant influence on the consumer behavior of college students of the Faculty of Economics, Padang State of University. Keywords : consumptive behavior, pocket money, life style.